Contexts for diversity and gender identities in higher education : international perspectives on equity and inclusion - Hoffman, Jaimie; Blessinger, Patrick; Makhanya, Mandla (Innovations in higher education teaching and learning ;, 2018)
This volume provides educators with an understanding of challenges associated with equity and inclusion at higher education institutions globally and with evidence-based strategies for addressing the challenges associated with implementing equity and inclusion. Higher education institutions continue to address an increasingly complex set of issues regarding equity, diversity and inclusion; many face increasing pressure to find innovative solutions for eliminating access and participation barriers and mitigating practices that impede access, persistence, retention, and graduation rates in higher education. Using comparative international perspectives, this volume looks at how different nations and cultures experience power, privilege, identity, and inclusion with respect to participation in tertiary education, with a specific focus on gender identities.